PUBLIC UTILITY FEES AS OWN REVENUES OF LOCAL SELF-GOVERNMENT UNITS IN THE TERRITORY OF AUTONOMOUS PROVINCE OF VOJVODINA - Cvjetković Ivetić, Cvjetana; Baturan, Luka (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The process of fiscal decentralization, as a typical feature of contemporary societies, implies the transfer of public functions and public revenues from higher to lower levels of authorities in order to ensure the financing of the transferred functions. The trend of fiscal decentralization has created the increased need for own revenues of local self-government units. The rates of these revenues are determined by local authorities, either independently or in line with the statutory limits. In the Republic of Serbia, own revenues of local self-government unit include different local public utility fees. In this paper, the authors deal with the financial autonomy of local self-government units observed through the lens of local public utility fees, (i.e. their yields), whereby the research will be limited only to the local self-government units in the territory of Autonomous Province of Vojvodina. The authors will also attempt to determine the factors that affect the rates and abundance of these revenues of local self-government units.